PENGARUH PEMBERIAN DOSIS PUPUK KANDANG DAN JENIS MULSA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SEMANGKA (Citrullus vulgaris,Schard) DI MUSIM HUJAN - Manurung, Masna; Sokip, Ahmad; Puspitorini, Palupi (Universitas Islam Balitar, 2016)
This research have go to influence interaction between cow manure and kind of mulch, also influence the best dose cow manure dan the best mulch to growth and water melon (Citrullus vulgaris,Schard) plant production at rainy season winner variety. The study has arranged by Random Designed Group (RAK) factorial with two treatments and 3 replications. Dose of cow manure in the first factor with 3 level,that is P1 = 5 ton- ha2 cow manure , P2 = 10 ton- ha2 and P3 = 15 ton-ha2. Second factor that is kind of mulch (M) with 3 level , that is M0 = no mulch, M1 = straw mulch and M2 = black silver mulch. Parameters that to be perceived to covet length of plant, leaf quantity, quality fruite and diameter fruite. The data is analyzed to use it analysis Of Variant (ANOVA), if influency to be continued with test DMRT 5%. The result of studies refer that, 1). Interactions between cow manure 10 ton-2 ( P2) silver and black mulch (M2) give the best influence in growing and watermelon plant productions. 2) giving fertilizer at all of treatment not influence about growing and water melon plant productions. 3) the kind of mulch treatment (M) give it influence about all of parameters . and black and silver mulch (M2) give the best treatment about growing and water melon plant productions.